Nobody’s perfect: can irregularities in pit structure influence vulnerability to cavitation? - Plavcová, Lenka; Jansen, Steven; Klepsch, Matthias; Hacke, Uwe G. (Frontiers in Plant Science, 2013)
Recent studies have suggested that species-specific pit properties such as pit membrane thickness, pit membrane porosity, torus-to-aperture diameter ratio and pit chamber depth influence xylem vulnerability to cavitation. Despite the indisputable importance of using mean pit characteristics, considerable variability in pit structure within a single species or even within a single pit field should be acknowledged. According to the rare pit hypothesis, a single pit that is more air-permeable than many neighboring pits is sufficient to allow air-seeding. Therefore, any irregularities or morphological abnormalities in pit structure allowing air-seeding should be associated with increased vulnerability to cavitation. Considering the currently proposed models of air-seeding, pit features such as rare, large pores in the pit membrane, torus extensions, and plasmodesmatal pores in a torus can represent potential glitches. These aberrations in pit structure could either result from inherent developmental flaws, or from damage caused to the pit membrane by chemical and physical agents. This suggests the existence of interesting feedbacks between abiotic and biotic stresses in xylem physiology.